Qudarat lord of the Pulangi [Book review] - Ortega, Christine Godinez; Perales, Jorge Ma. Cui (2006)
Qudarat: lord of the Pulangi by Jorge Ma. Cui-Perales, published in Manila by the University of Santo Tomas Publishing House, 2001. 214 pp.